Pengaruh Kompetensi Kepribadian Guru PAK terhadap Karakter Siswa Kelas XI Tata Busana SMK Negeri 1 Laguboti Kabupaten Toba Tahun Pembelajaran 2023/2024 - Lewina Karine Tampubolon; Elvri Teresia Simbolon; Nisma Simorangkir (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2024)
The purpose of this study was to determine the extent of the influence of the personality competence of PAK teachers on the character of students in class XI of cosmetology of SMK Negeri 1 Laguboti, Toba Regency for the 2023/2024 learning year, with the hypothesis that there is a positive and significant influence of the influence of the personality competence of PAK teachers on the character of students in class XI of cosmetology of SMK Negeri 1 Laguboti, Toba Regency for the 2023/2024 Learning Year. With a population of all students in class XI of Fashion Management of SMK Negeri 1 Laguboti who are Protestant Christians totaling 90 people with a sample of 60 people so that this study uses descriptive methods with cluster sampling techniques. Data were collected with a 54-item closed questionnaire prepared by the author based on variable indicators according to expert theory. The questionnaire test was conducted on 30 respondents of Class XI of Fashion Management 1 SMK Negeri 1 Laguboti Toba Regency for the 2023/2024 Learning Year using 54 questionnaire items and after being tested the results of the validity of the questionnaire test were known to be the value of rcount> rtable = 0.142-0.604 (there are 8 items of question items that have a validity of less than rtable 0.361 so that invalid questionnaires are discarded). Thus the valid questionnaire amounted to 46 question items. And the reliability of the questionnaire test which is at a value of 0.607. The results of data analysis show that there is a positive influence and significant between the Personality Competence of PAK Teachers on the Character of Students in Class XI of Fashion Management at SMK Negeri 1 Laguboti, Toba Regency for the 2023/2024 Learning Year. With the relationship test obtained rcount> rtable, namely 0.343>0.254, with a significant relationship test tcount> ttable, namely 3.654>2.000, with a linear regression test = α + bx = 26.98 + 0.248X. This equation shows that in a constant state of 26.98, for each addition of variable X (Teacher Personality Competence) by one unit, there will be an addition to variable Y (Student Character) of 0.248 from (variable X), the coefficient of determination is 11.76%. This means that Ho is rejected and Ha, accepted. Significant test of influence with Fcount>Ftabel (7.752>4.00) means that there is a positive and significant influence between the Personality Competence of PAK Teachers on the Character of Students in Class XI of Fashion Management at SMK Negeri 1 Laguboti, Toba Regency for the 2023/2024 Learning Year. This study suggests that teachers should always improve their Personality Competence as a PAK Teacher, so that the Character of Students in Class XI of Fashion Management at SMK Negeri 1 Laguboti, Toba Regency in the 2023/2024 Learning Year will be better.